Multiple Eruptive Dermatofibromas in a Patient with Primary Sjögren’s Syndrome - Kaya, Mehmet Nur; Tecer, Duygu; Yılmaz, Sedat (European Journal of Therapeutics, 2023)
Multiple eruptive dermatofibromas (MEDF) are rare tumors and thought to be associated with the disturbances in the immune system. In our 40-year-old case, 5 nodules have developed in a 4-month period. The patient was diagnosed by a dermatologist to have MEDF, and referred to rheumatology outpatient clinic because of the symptoms such as dry mouth, and polyarthralgia. After clinical and laboratory evaluation, the diagnosis of primary Sjögren’s syndrome (SS) was made. According to the best of our knowledge, this case is the first reported association between MEDF and primary SS. Therefore, when the diagnosis of MEDF is made, SS should also been included in the comprehensive evaluation of associated diseases.